Wokół Forum - Bieńkowska, Ewa (Poznańskie Studia Polonistyczne. Seria Literacka, 2009)
The essay is excerpted from a chapter of a book that is currently being written by the author. The working title of the book is Spacery po kościołach rzymskich [Walks through historical churches and temples of Rome] (Wydawnictwo Zeszytów Literackich). The present essay aims at discussing the specific character of the Christian church architecture of the city of Rome that constitutes nodes of a network that has been developing throughout one and a half millennia. Each of the chapters of the book is centered around a particular walk of the town that includes on its way the described churches. The walks cover virtually the whole of the old town and some of the adjacent palaces. The adopted method of presentation is purely personal and has a character of a “Roman diary” — to some extent, the author has been inspired by Promenades das Rome by Stendhal. The diary is, however, a particular guide book on the town for those who want to experience something else that the offer presented by standard guidebooks. Notwithstanding it subjective angle, the book does not interfere in passing the essential historical and artistic knowledge to the reader. Rome appears here to be a singular place, as a personification of one of the most important stages of Western civilization.